Real-space evidence of the equilibrium ordered bicontinuous double diamond structure of a diblock copolymer1. Issue 10 (14th March 2015) - Chu, C. Y.; Jiang, X.; Jinnai, H.; Pei, R. Y.; Lin, W. F.; Tsai, J. C.; Chen, H. L.
<x xml:space="preserve">Abstract</x> A thermally stable ordered bicontinuous double diamond (OBDD) structure in a stereoregular diblock copolymer has been revealed by electron tomography. The structure underwent a thermally reversible transition to double gyroid upon heating, accompanied by a reduction of domain spacing.